2003
DOI: 10.1038/sj.npp.1300310
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana Withdrawal in Humans: Effects of Oral THC or Divalproex

Abstract: Abstinence following daily marijuana use can produce a withdrawal syndrome characterized by negative mood (eg irritability, anxiety, misery), muscle pain, chills, and decreased food intake. Two placebo-controlled, within-subject studies investigated the effects of a cannabinoid agonist, delta-9-tetrahydrocannabinol (THC: Study 1), and a mood stabilizer, divalproex (Study 2), on symptoms of marijuana withdrawal. Participants (n ¼ 7/study), who were not seeking treatment for their marijuana use, reported smoking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
228
1
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 241 publications
(246 citation statements)
references
References 35 publications
14
228
1
3
Order By: Relevance
“…Neither medication alone had this effect. Although THC decreases nicotine withdrawal in mice (Balerio et al, 2004), smoking behavior during marijuana abstinence was not decreased by THC either in this study or in our earlier study (Haney et al, 2004). Clonidine appears to decrease smoking in clinical trials compared to placebo, but side effects decrease clonidine's potential to treat nicotine dependence (see Covey et al, 2000).…”
contrasting
confidence: 69%
See 3 more Smart Citations
“…Neither medication alone had this effect. Although THC decreases nicotine withdrawal in mice (Balerio et al, 2004), smoking behavior during marijuana abstinence was not decreased by THC either in this study or in our earlier study (Haney et al, 2004). Clonidine appears to decrease smoking in clinical trials compared to placebo, but side effects decrease clonidine's potential to treat nicotine dependence (see Covey et al, 2000).…”
contrasting
confidence: 69%
“…The antidepressant, nefazodone, which is sedating compared to the stimulant-like bupropion, decreased a subset of marijuana withdrawal symptoms (Haney et al, 2003), but the medication that most effectively attenuated marijuana withdrawal was THC (dronabinol, Marinol). THC selectively decreased ratings of anxious, miserable, trouble sleeping, chills, and marijuana craving, and reversed the large decreases in food intake during marijuana abstinence as compared to placebo, while producing no cannabinoid intoxication (Haney et al, 2004). These results have recently been replicated in an outpatient setting (Budney et al, 2007).…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…The latter consists of a constellation of symptoms similar to those seen with nicotine withdrawal, which include irritability, sleep difficulty, decreased appetite, weight loss, and increased anger and irritability (Kouri et al, 1999;Kouri and Pope, 2000;Budney et al, 2003). There have been few pharmacological attempts to alleviate this syndrome (McRae et al, 2003), but one approach using oral D 9 -THC has recently shown significant promise (Haney et al, 2004). The broad applicability of a replacement therapy may be limited, however, by undesirable psychotropic and cardiovascular side effects.…”
Section: Discussionmentioning
confidence: 99%